Genome-wide identification of galactinol synthase (GolS) genes in Solanum lycopersicum and Brachypodium distachyon. (October 2015) - Filiz, Ertugrul; Ozyigit, Ibrahim Ilker; Vatansever, Recep
Highlights: Galactinol synthase ( GolS ) genes have been identified at genome-wide scale in Solanum lycopersicum and Brachypodium distachyon species. The results of this study can contribute to understanding of the structure and biological role of GolS genes/proteins in different plant species. Abstract: GolS genes stand as potential candidate genes for molecular breeding and/or engineering programs in order for improving abiotic stress tolerance in plant species. In this study, a total of six galactinol synthase ( GolS ) genes/proteins were retrieved for Solanum lycopersicum and Brachypodium distachyon . GolS protein sequences were identified to include glyco_transf_8 (PF01501) domain structure, and to have a close molecular weight (36.40–39.59 kDa) and amino acid length (318–347 aa) with a slightly acidic pI (5.35–6.40). The sub-cellular location was mainly predicted as cytoplasmic. S. lycopersicum genes located on chr 1 and 2, and included one segmental duplication while genes of B. distachyon were only on chr 1 with one tandem duplication. GolS sequences were found to have well conserved motif structures. Cis-acting analysis was performed for three abiotic stress responsive elements, including ABA responsive element (ABRE), dehydration and cold responsive elements (DRE/CRT) and low-temperature responsive element (LTRE). ABRE elements were found in all GolS genes, except for SlGolS4 ; DRE/CRT was not detected in any GolS genes and LTRE element found in SlGolS1 and BdGolS1 genes. AU analysis in UTR and ORF regions indicated that SlGolS and BdGolS mRNAs may have a short half-life. SlGolS3 and SlGolS4 genes may generate more stable transcripts since they included AATTAAA motif for polyadenylation signal POLASIG2. Seconder structures of SlGolS proteins were well conserved than that of BdGolS. Some structural divergences were detected in 3D structures and predicted binding sites exhibited various patterns in GolS proteins.